Role Of Teacher to Enhance the Interfaith Tolerance Among the Students: In the Light of Islam - Dr Khadija Akbar Khan; Sumaira Bashir; Dr. Irfan Jafar (International Research Journal of Arabic and Islamic Studies, 2024)
The term “interfaith tolerance” means for the people belonging to different religions or to different groups of the same religion to behave warmly, discuss and debate the common matters and cooperate together without trying to impose their thoughts and beliefs upon other people. It involves promoting understanding between different religions to increase acceptance of others, rather than to synthesize new beliefs. The objectives of the study were to examine the existing level of interfaith tolerance among students, to find the effect of classroom activities on the tolerance level of students and to confirm that teaching according the Islam increases the interfaith tolerance level of the students. It is raised a question that what is the existing level of interfaith tolerance among students? What is the effect of classroom activities on the tolerance level of students? Does the teaching according to Islam enhance the level of interfaith tolerance among the students? The research work will guide to the parent, teaching community and every person in understanding the role of teacher to enhance the interfaith tolerance among the students and to identify the problems related to training of interfaith tolerance, to make those problems understandable and also projecting their solutions in the light of the teachings of the Islam. It is a six-month long study the subjects will be two intact groups who are studying in the school. Tolerance Scale will be developed for the study. The study will be conducted in two different phases. At the first phase the Tolerance Scale will be administered to the subjects as a pre-test. In the 2nd phase the experimental group will be taught teachings of Islam for six months. After six months the Tolerance Scale will be re administered to record the change in the level of tolerance. The data will be collected. The results will be found and analyzed and recommendations will be presented for increasing the tolerance level of the elementary school students.